The genus Pycnolejeunea (Lejeuneaceae, Marchantiophyta) in Thailand, with the description of Pycnolejeunea zhuiana - Chatchaba Promma; Sahut Chantanaorrapint (PhytoKeys)
A taxonomic study of the genus Pycnolejeunea in Thailand is presented, based on herbarium specimens and new collections from field surveys. Three species are recognised including P. contigua, P. grandiocellata and one new species, P. zhuiana. The new species is distinguished by the strongly papillose lobules, the presence of 1–8 basal ocelli on the lateral leaf and male bracteoles occurring along nearly the whole of the androecial branch length. A key to species, descriptions and illustrations are provided; ecology and geographical distribution of the species are also described.